The Rabbinic Citation Network - Satlow, Michael L. (AJS review, 2022)
This article is the first academic attempt to apply quantitative methods of social network analysis to the Babylonian Talmud. We make three contributions. First, we introduce a digital methodology for finding and analyzing the citation chains in the Bavli. Second, we use our analysis to show the general characteristics of this network, which we find to be limited, densely connected, and centered around just a few rabbis at its center. Finally, we discuss three use cases that point toward further research that could throw light on the redactorial process of the Babylonian Talmud. This research lays the groundwork for much future work in applying quantitative methods to rabbinic texts.